2015 USNC-URSI Radio Science Meeting (Joint With AP-S Symposium) 2015
DOI: 10.1109/usnc-ursi.2015.7303445
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion engineering via nonlocal transformation optics

Abstract: Transformation optics (TO) has established itself as a powerful and versatile approach to the synthesis of metamaterials with prescribed field-manipulation capabilities, via suitable spatial modulation of their constitutive properties inspired by local distortions of the spatial coordinate reference frame. From the mathematical viewpoint, this approach can be reformulated in the frequency-wavenumber reciprocal phase space so as to engineer nonlocal interactions and spatial dispersion effects, which are becomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…For instance, we showed that (non)reciprocal effects and the appearance of additional extraordinary waves [6] are directly related to the (non-)centersymmetry and multivaluedness, respectively, of the transformations [13]. Moreover, we derived the analytical properties of classes of transformations that could induce stationary points in the dispersion diagram, and we also showed that frequency-dependent wavevector transformations enable a finer tailoring in the phase space, thereby opening up the possibility to engineer complex spatio-temporal dispersion effects such as Dirac-point conical singularities [14].…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…For instance, we showed that (non)reciprocal effects and the appearance of additional extraordinary waves [6] are directly related to the (non-)centersymmetry and multivaluedness, respectively, of the transformations [13]. Moreover, we derived the analytical properties of classes of transformations that could induce stationary points in the dispersion diagram, and we also showed that frequency-dependent wavevector transformations enable a finer tailoring in the phase space, thereby opening up the possibility to engineer complex spatio-temporal dispersion effects such as Dirac-point conical singularities [14].…”
Section: Introductionmentioning
confidence: 89%
“…In reference [14], within the framework of nonlocal TO, we derived a class of wavevector transformations that could induce stationary points (of arbitrary order) in the dispersion relationship. In particular, we explored in detail the case m = 3 in equations (1) and (2), corresponding to the ''frozenmode'' regime.…”
Section: Ideal Constitutive Blueprintsmentioning
confidence: 99%
See 3 more Smart Citations